Totalitarism in The Handmaid’s Tale: between manipulation and programming - Resende, Natália Silva Giarola de; Mendes, Conrado Moreira (Faculdade de Ciências e Letras - Unesp - Araraquara., 2020)
In this paper, based on the regimes of meaning and interaction from sociosemiotics theory (LANDOWSKI, 2014), we aim to understand how the totalitarian regime of Gilead, a fictional nation in the dystopian series The Handmaid’s Tale, is constituted, taking as object of analysis the first episode, entitled Offred. From the articulation between the theoretical foundations – totalitarianism (ARENDT, 2012; NEUMANN, 1969; TURPIN, 2012) and sociosemiotics – and the reflections resulting from the analysis, we verified that both the manipulation and programming regimes legitimize the conservation of the totalitarian state.